Capecitabine-associated hand-foot-skin reaction is an independent clinical predictor of improved survival in patients with colorectal cancer - Hofheinz, Ralf-Dieter; Gencer, Deniz (British journal of cancer, 2012)
Background: Hand-foot-skin reaction (HFSR) is an adverse event frequently observed during treatment with capecitabine (cape). In the present analysis, we sought to evaluate the potential association of HFSR and survival in German patients with metastatic colorectal cancer and locally advanced rectal cancer treated with cape in clinical trials. Methods: Patients of the Arbeitsgemeinschaft für Internistische Onkologie (AIO) KRK-0104 and the Mannheim rectal cancer trial were evaluated. HFSR was graded according to NCI-CTC criteria in both trials. Time to first occurrence of HFSR was described per cycle and HFSR developing during cycles 1 and 2 was defined as ‘early HFSR’. Baseline characteristics between the patient groups with or without HFSR were compared using Mann-Whitney-U, Fisher’s exact or χ2-test, as appropriate. Haematological and non-haematological toxicities observed in both groups were compared using Fisher’s exact test. Progression-free (PFS) or disease-free (DFS) as well as overall survival (OS) data from both trials were pooled and the HFSR group was compared with the non-HFSR using Kaplan-Meier analysis. Results: A total of 374 patients were included, of whom 29.3% developed any HFSR. Of these, 51% had early HFSR. Baseline characteristics were comparable between both HFSR groups concerning age, gender, ECOG performance status and UICC stage. On multivariate analysis none of these factors had influence on the occurrence of HFSR. The percentage of all-grade (and grade 3-4) haematological toxicities did not differ between both the groups. By contrast, patients exhibiting HFSR had a significantly higher rate of all-grade (but not grade 3-4) diarrhoea, stomatitis/mucositis and fatigue (P<0.01, respectively). Patients with HFSR had improved PFS/DFS (29.0 vs 11.4 months; P=0.015, HR 0.69) and OS (75.8 vs 41.0 months; P=0.001, HR=0.56). Within the HFSR group, PFS/DFS and OS were comparable between patients with early vs late HFSR. Interpretation: The present analysis provides evidence for the association of HFSR and survival in patients with colorectal cancer. Baseline characteristics, with the exception of UICC stage, older age and ECOG performance status, and the time of occurrence of HFSR had no impact on survival. Patients with HFSR had a higher probability of developing any-grade gastrointestinal toxicity and fatigue while no correlation with haematological toxicity was found.